Predictor of Diabetes: Correlation between Leucine Concentration and Insulin Resistance - Wijaya, Chyntia R.; Sukmana, Indriyanti R.; Levita, Jutti (Pharmacology and Clinical Pharmacy Research)
Leucine catabolism changes among people with central obesity. This condition can lead to metabolic pathway disorder and increased mTORC-1 activation. Downstream signal of mTORC-1 is p70S6K1, which causes phosphorylation of insulin-1 receptor substrate (IRC-1). This study was performed to evaluate correlation between leucine concentration and insulin resistance (IR). This study was a prospective cross-sectional study, involving two groups; control and obese group. General characteristics and blood sample were taken from each subject. Leucin and Homeostasis Model Assesment (HOMA)-IR, as the marker of insulin resistance, were evaluated. The result indicated a significant positive correlation between leucine concentration and insulin resistance value (R=0.351; P=0.006) in central obese men. The higher leucine concentration, the higher the risk of insulin resistance occurrance. Therefore, leucine can be used as a biomarker for early detection of insulin resistance.Keywords: amino acids, mTORC-1, insulin-1 receptor substrate